Relationship between magnetic properties and reddening of tropical soils as indicators of weathering - Preetz, Holger; Igel, Jan; Hannam, Jacqueline A.; Stadler, Susanne (Elsevier, 2017)
This study evaluates the use of magnetic properties as an indicator of weathering of tropical soils. Soil samples collected across the tropical belt were analysed for magnetic susceptibility and its frequency dependence. Frequency dependence is caused by superparamagnetic (SP) ferrimagnetic nanoparticles, which are commonly attributed to neoformation during soil forming processes. Magnetic properties are compared to the redness rating of soil colour, which is related to the hematite content and is an established proxy for soil weathering. The investigated samples comprise material of different weathering stages from unweathered and weathered rock to subsoil and strongly weathered topsoil. They cover a broad variety of parent materials: ultrabasic, basic, intermediate, acid igneous rocks, clays and clay slates, phyllites and sandstones. The results show that soil reddening, magnetic susceptibility and in particular frequency-dependent susceptibility generally increase with proceeding weathering. However, there is a lithologic overprint and the parent material has to be taken into consideration. Soils stemming from acid igneous rocks, clays, clay slates and phyllites show a positive correlation between reddening and susceptibility or frequency dependent susceptibility, rendering these properties suitable for indicating weathering. In contrast, soils stemming from ultrabasic, basic and intermediate igneous rocks and sandstones show no significant correlation. The reason is the strong lithogenic overprint of ferrimagnetic minerals including SP particles, which commonly occur in these rock types.
Keywords: Tropical soil; Laterite; Soil development; Iron oxide; Reddening; Magnetic susceptibility